Die musik des griechischen alterthumes Nach den alten Quellen neu bearbeitet - Westphal, Rudolf 1826-1892 (Cambridge library collection. Classics, 1883)
The German classical philologist Rudolf Westphal (1826─92) had originally studied theology at the University of Marburg before turning his attention to comparative linguistics. He learnt Sanskrit and Arabic and took a keen interest in Indo-European languages and Semitic grammar. In the late 1850s and early 1860s he joined his friend and fellow philologist August Rossbach (1823–98) at the University of Breslau (Wrocław) and later taught at Moscow's Imperial Lyceum. In this 1883 work, he gives an extensive account of melody and rhythm in ancient Greek music. Westphal is full of admiration for the philosopher Aristoxenus (born c.370 BCE), whom he hails as 'the founder of musicology'. Following Aristoxenus' distinction between melody (quality of tone) and rhythm (quantity of tone), Westphal divides his work into two parts that describe and exemplify these components in detail. His multi-volume Theorie der musischen Künste der Hellenen is also reissued in this series